Secure PHP Development: Building 50 Practical Applications - Kabir, Mohammed J. (Wiley Publishing, 2011)
Offers fifty practical and secure PHP applications that readers can immediately put to use * Explains the entire life cycle of each PHP application, including requirements, design, development, maintenance, and tuning * Reviews application development line-by-line and module-by-module to help readers understand specific coding practices and requirements * Applications can be readily adapted to many real-world business situations * CD-ROM contains fifty ready-to-use PHP applications, an evaluation version of Zend tools, and the latest versions of PHP, Apache, and MySQL